2015
DOI: 10.1016/j.celrep.2015.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-Rich Lipoproteins Modulate the Distribution and Extravasation of Ly6C/Gr1low Monocytes

Abstract: SummaryMonocytes are heterogeneous effector cells involved in the maintenance and restoration of tissue integrity. However, their response to hyperlipidemia remains poorly understood. Here, we report that in the presence of elevated levels of triglyceride-rich lipoproteins, induced by administration of poloxamer 407, the blood numbers of non-classical Ly6C/Gr1low monocytes drop, while the number of bone marrow progenitors remains similar. We observed an increased crawling and retention of the Gr1low monocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…Consistent with the previous outcomes of Professor Saja17, we found that P-407 could elevate the serum ApoCIII levels which affected the metabolism of triglyceride and induced hypertriglyceridemia (Fig. S1A).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with the previous outcomes of Professor Saja17, we found that P-407 could elevate the serum ApoCIII levels which affected the metabolism of triglyceride and induced hypertriglyceridemia (Fig. S1A).…”
Section: Resultssupporting
confidence: 91%
“…Saja et al 17. also verified that long-term HTG could cause lipid deposition and macrophages infiltration in heart, liver and kidney.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Scale bars: 100 μm (B-E). (31,53), it has now become questionable whether CX3CR1 is important for the process of Ly6C lo monocyte recruitment or not (50). There have also been reports suggesting that CX3CR1 deficiency influences the survival of monocytes (54,55).…”
Section: Anti-vegfr2 Therapy Induces Accumulation Of Monocytes and Nementioning
confidence: 99%
“…(4) A second subset denoted as “patrolling” or anti-inflammatory monocytes that express Ly6C low CCR2 low CX 3 CR1 high in mice and CD14 + CD16 + in humans, recruit to inflamed endothelium early in the process of lesion formation, give rise to CD11c + foamy macrophages, and extravasate at the endothelial interface and accumulate in organs. (7, 8) The propensity for the trafficking and emigration of specific monocyte subsets is dictated by their relative expression of chemokine C-C motif receptor 2 (CCR2), C-C motif receptor 5 (CCR5), and chemokine C-X 3 -C motif receptor 1 (CX 3 CR1) that signal integrin activation and guide cell migration to arterial sites of nascent plaque formation. (7, 8) A direct comparison of inflammatory activation in the context of lipid mediated integrin-dependent recruitment on VCAM-1 between mouse and human monocyte subsets is lacking.…”
Section: Introductionmentioning
confidence: 99%